Psychological variables involved in teacher’s job performance - Torres Valladares, Manuel (2008)
The purpose of this study is to analyze the casual relations that can exist between some psychological variables (Personality Type A, Stress facing and Burnout Syndrome) and the labour performance of university teachers from  five faculties of medicine of Lima Metropolitana. The instruments used were: Blumenthal’s inventory of auto report of behaviour type A, COPE, Maslasch’s Burnout inventory and the teacher’s labour performance made by Manuel Fernández Arata. All these instruments were subjected to the respective analysis in order to determinate their validity and reliability. The sample was constituted by 150 doctors teachers to whom the questionnaires were applied. The results show that Personality Type A, Stress Facing and Burnout Syndrome have influence over their labour performance, so is necessary that universities develop specific programmes that allow teachers manage their emotions in an efficient way.